Was There a Soviet Nationality Policy?. Issue 6 (3rd July 2019) - Smith, Jeremy
Abstract: The essay challenges the frequent references to the concept of Soviet nationality policy by historians and social scientists. The argument proceeds, first, by unpicking some of the logic in the use of the term; second, by examining the evidence for the existence and nature of such a policy; and third, by considering alternative explanations for major decisions and events concerning non-Russian nationalities in the Soviet Union. The essay concludes that, at least after the 1920s, there was no Soviet nationality policy, and the processes of negotiation and nation-promoting practices pursued by republic leaders were, instead, the key influences on decision-making.